Genetic liability for diet-derived circulating antioxidants, oxidative stress, and risk of osteoarthritis: a Mendelian randomization study - Tang, Yidan; Xu, Xiaolin; Zhang, Shuangyi; Kong, Weishuang; Zhang, Weiyi; Zhu, Tao (Frontiers in Nutrition, 2023)
Background: Though well-documented, the causal relationships between diet-derived circulating antioxidants, oxidative stress, and osteoarthritis (OA) are equivocal. The objective of this study is to employ two-sample Mendelian randomization (MR) to investigate possible causal relationships between dietary-derived circulating antioxidants, oxidative stress damage indicators, and OA risk.Methods: Single-nucleotide polymorphisms for diet-derived circulating antioxidants (ascorbate, βcarotene, lycopene, retinol, α-and γ-tocopherol), assessed as absolute levels and metabolites, as well as oxidative stress injury biomarkers (GSH, GPX, CAT, SOD, albumin and total bilirubin), were retrieved from the published data and were used as genetic instrumental variables. Summary statistics for gene-OA associations were obtained from publicly available and relatively two large-scale GWAS meta-analyses to date. The inverse-variance weighting method was utilized as the primary MR analysis. Moreover, multivariable MR were used to determine if mediators (BMI and smoking) causally mediated any connection. Furthermore, for each exposure, MR analyses were conducted per outcome database and then meta-analyzed.Results: Genetically predicted the absolute retinol level was causally associated with hip OA risk [odds ratios (ORs) = 0.40, 95% confidence interval (CI) = 0.24-0.68, FDR-corrected p = 0.042]. Besides, genetically predicted albumin level was causally associated with total OA risk (OR = 0.80, 95% CI = 0.75-0.86, FDR-corrected p = 2.20E-11), as well as the risk of hip OA (OR = 0.75, 95% CI = 0.68-0.84, FDR-corrected p = 1.38E-06) and knee OA (OR = 0.82, 95% CI = 0.76-0.89, FDR-corrected p = 4.49E-06). Besides, MVMR confirmed that the effect of albumin on hip OA is independent of smoking initiation, alcoholic drinks per week and moderate to vigorous physical activity levels, but may be influenced by BMI.Conclusions: Evidences from our study support a potentially protective effect of high levels of retinol and albumin on OA risk.